Rare occurrence of type lll membranoproliferative glomerulonephritis in a patient with hepatitis C in sustained virologic response phase - Tan, Yi Jun; Then, Ru Fah; Lim, Christopher Thiam Seong (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Hepatitis C virus (HCV) infection is known to cause acute and chronic active hepatitis. In addition, HCV also has systemic disorder involvement that links to various extra-hepatic complications. We report a case of a patient which has been diagnosed to have Hepatitis C Genotype 3A who has been started on antiviral. He achieved end treatment response and sustained virologic response. During routine follow up, he experienced acute kidney injury. Renal biopsy showed type III membranoproliferative glomerulonephritis. His proteinuria improved greatly with the addition of angiotensin converting enzyme inhibitor. This case highlights the possibility of appearance of HCV related glomerulonephritis in patient who has sustained virological response.